Invaders taking over—Mollusc faunal change in volcanic barrier lakes of the Albertine Rift biodiversity hotspot - Francis Ssenkuba; Marcellin Rwibutso; Marie Claire Dusabe; Julius Tumusiime; Christian Albrecht (PLoS ONE, 2026)
East African freshwater are renowned biodiversity hotspots, particularly within the Rift Valley lakes, which exhibit exceptional species richness and endemism. However, research in this region has predominantly focused on large Rift lakes, with smaller volcanic barrier lakes remaining underexplored. This study integrated morphological, DNA barcoding, and ecological analyses to assess mollusc diversity, biogeographical affinities, environmental correlates of distribution, and community differences in lakes Bunyonyi, Mutanda, and Mulehe in Uganda, and Lakes Ruhondo and Burera in Rwanda. Results revealed a relatively high malacofaunal diversity in these lakes compared to some Great Lakes in the region, although these comparisons should be interpreted cautiously because sampling scope differs among studies. Assemblages largely exhibited Nilotic affinities and were dominated by widespread mollusc species. Our findings suggest ongoing homogenisation of mollusc communities, as indicated by reduced dispersion among invaded lakes. While this pattern is consistent with potential influences of anthropogenic activities and invasive species such as the North American crayfish ( Procambarus clarkii ), Physella acuta , and the Asian lineage of Melanoides tuberculata , our analyses do not allow us to disentangle invasion effects from other confounding factors, including lake-specific characteristics and environmental gradients . Therefore, invasion-driven homogenisation should be interpreted with caution. Nevertheless, this trend, coupled with habitat degradation from agriculture, pollution, and infrastructure development, may pose significant threats to the mollusc diversity in these lakes. This research underscores the importance of prioritising these overlooked, fragile ecosystems in the regional biodiversity conservation strategies to safeguard habitats for molluscs and other faunal elements. A comprehensive regional freshwater survey, including metabarcoding, is needed to document molluscan diversity patterns under ongoing environmental change and increasing anthropogenic pressure.